Job Satisfaction, Organizational Commitment and Organizational Citizenship Behavior of High School Principals - Musringudin Musringudin; Yulian Dinihari; Afriantoni Afriantoni (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aimed to measure the influence of job satisfaction and organizational commitment on the principal's organizational citizen behaviour (OCB). The kind of research was quantitative with a method of survey. The research population was 116 people. With the Proportional Random Sampling technique, the sample used was 90 people. Data collection was done by distributing questionnaires. The techniques of data analysis were descriptive analysis and inferential statistics. The results indicated an effect of job satisfaction on Organizational Citizenship Behaviour (OCB). The positive effect of organizational commitment on organizational citizenship behaviour and job satisfaction also positively influenced organizational commitment. This research has implications for principals' organizational citizenship behaviour was able to be increased to improve organizational justice, improvement and enhancement of job satisfaction and organizational commitment will affect the improvement of organizational citizenship behaviour of principals.